2016
DOI: 10.1016/j.amjmed.2016.02.044
|View full text |Cite
|
Sign up to set email alerts
|

A Blend of Sesame and Rice Bran Oils Lowers Hyperglycemia and Improves the Lipids

Abstract: A novel blend of 20% cold-pressed unrefined sesame oil and 80% physically refined rice bran oil as cooking oil, lowered hyperglycemia and improved the lipid profile in type 2 diabetes mellitus patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
0
26
1
1
Order By: Relevance
“…Our results do not correspond with studies showing significantly decreased levels of TGs [14,15,17,25]. Kuriyan and colleagues used RBO for daily cooking so that it did not change the proportion of daily fat intake.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results do not correspond with studies showing significantly decreased levels of TGs [14,15,17,25]. Kuriyan and colleagues used RBO for daily cooking so that it did not change the proportion of daily fat intake.…”
Section: Discussioncontrasting
confidence: 99%
“…Changes in blood glucose levels upon RBO administration in the present study were not significantly different from those recorded in other studies. In research conducted by Devarajan and colleagues using a mixture of RBO with sesame seeds in a large study for 8 w, changes in blood glucose levels showed a significant change (p<0.001) [17].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Devarajan et al . () reported that HDL‐c levels increased significantly in hypertensive patients treated with sesame oil.…”
Section: Discussionmentioning
confidence: 97%